Kinome-wide RNAi screening for mediators of ABT-199 resistance in breast cancer cells identifies Wee1 as a novel therapeutic target. (August 2021) - Aka, Yeliz; Karakas, Bahriye; Acikbas, Ufuk; Basaga, Huveyda; Gul, Ozgur; Kutuk, Ozgur
Abstract: Antiapoptotic and proapoptotic BCL-2 protein family members regulate mitochondrial apoptotic pathway. Small molecule inhibitors of antiapoptotic BCL-2 proteins including BCL-2-specific inhibitor ABT-199 (Venetoclax) are in clinical development. However, the efficiency of ABT-199 as a single agent in solid tumors is limited. We performed a high-throughput RNAi kinome screen targeting 691 kinases to identify potentially targetable kinases to enhance ABT-199 response in breast cancer cells. Our studies identified Wee1 as the primary target kinase to overcome resistance to ABT-199. Depletion of Wee1 by siRNA-mediated knockdown or inhibition of Wee1 by the small molecule Wee1 inhibitor AZD1775 sensitized SKBR3, MDA-MB-468, T47D and CAMA-1 breast cancer cells to ABT-199 along with decreased MCL1. BH3-only proteins PUMA and BIM functionally contribute to apoptosis signaling following co-targeting BCL-2 and Wee1. Suppression of Wee1 function increased mitochondrial cell death priming. Furthermore, we found that Wee1 inhibition altered MCL1 phosphorylation and protein stability, which led to HUWE1-mediated MCL1 degradation. Our findings suggest that Wee1 inhibition can overcome resistance to ABT-199 and provide a rationale for further translational investigation of BCL-2 inhibitor/Wee1 inhibitor combination in breast cancer.